Application of the multilevel matrix decomposition algorithm to the frequency analysis of large microstrip antenna arrays - Parron, J.; Rius, J.M.; Mosig, J.R. (IEEE transactions on magnetics, 2002)
The application of integral equation methods based on the method of moments discretization to solve large antenna arrays is difficult due to the fact that the computational requirements increase rapidly with the number of unknowns. This is critical when a frequency analysis of the antenna is required. We propose the multilevel matrix decomposition algorithm (MLMDA) to carry out this purpose efficiently. As the MLMDA method is particularly well-suited for the analysis of planar structures with any Green's function, it is a very efficient approach for the frequency analysis of microstrip antenna arrays.